2021
DOI: 10.3390/ma14061499
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adhesive Layer Thickness on Joint Static Strength

Abstract: One of the most relevant geometrical factors defining an adhesive joint is the thickness of the adhesive layer. The influence of the adhesive layer thickness on the joint strength has not been precisely understood so far. This article presents simplified analytical formulas for adhesive joint strength and adhesive joint coefficient for different joint loading, assuming, inter alia: linear-elastic strain of adhesive layer, elastic strain of adherends and only one kind of stress in adhesive. On the basis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Figure 11a shows that as t A increases, the peeled area rate decreases. This behavior can be explained by the fact that the trigger load increases with increasing adhesive thickness, especially in the range of 0.01-0.08 mm, as reported by Roskowicz et al in [23]. The results also reveal that the robot approaching velocity v R does not influence the PA; thus, it can be reasonably set at high values in order to reduce the task execution time.…”
Section: Resultssupporting
confidence: 64%
“…Figure 11a shows that as t A increases, the peeled area rate decreases. This behavior can be explained by the fact that the trigger load increases with increasing adhesive thickness, especially in the range of 0.01-0.08 mm, as reported by Roskowicz et al in [23]. The results also reveal that the robot approaching velocity v R does not influence the PA; thus, it can be reasonably set at high values in order to reduce the task execution time.…”
Section: Resultssupporting
confidence: 64%
“…The compression of the adhesive layer is considered to be the reason for the improvement of adhesion strength. The previous report showed that thin adhesive layers are more beneficial than thick ones 32 , and larger quantities did not increase the adhesion strength of our system (Supplementary Fig. 40 ) as the adhesive layer became thick.…”
Section: Resultsmentioning
confidence: 46%
“…It is also important to bear in mind that despite the uniform applied pressure to the joint during curing, it is not possible to guarantee an exact uniformity of the adhesive layer thickness among all tested joints. The effect of the adhesive thickness on bond strength, which would depend on the epoxy mechanical characteristics and on the type of joint, is complex and not yet fully understood [ 28 , 29 , 30 ]. Large variations on the adhesive thickness may even produce changes on the cohesive/adhesive failure mode [ 28 ], although this is not expected to occur in the present work, given the above-mentioned thickness range measured in selected joints of this study.…”
Section: Resultsmentioning
confidence: 99%